2014
DOI: 10.1136/thoraxjnl-2014-206225
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of GDF-15 may mediate ICU-acquired weakness by down-regulating muscle microRNAs

Abstract: RationaleThe molecular mechanisms underlying the muscle atrophy of intensive care unit-acquired weakness (ICUAW) are poorly understood. We hypothesised that increased circulating and muscle growth and differentiation factor-15 (GDF-15) causes atrophy in ICUAW by changing expression of key microRNAs.ObjectivesTo investigate GDF-15 and microRNA expression in patients with ICUAW and to elucidate possible mechanisms by which they cause muscle atrophy in vivo and in vitro.MethodsIn an observational study, 20 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 36 publications
3
89
1
6
Order By: Relevance
“…Interestingly, an increased expression of GDF-15 was associated with a reduced expression of some microRNAs involved in the regulation of muscle growth in patients hospitalized in intensive care (Bloch et al 2015). These findings suggest a direct role of GDF15 as a suppressor of muscle growth potentially involved in sarcopenia and, therefore, support GDF15 as a reliable biomarker.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…Interestingly, an increased expression of GDF-15 was associated with a reduced expression of some microRNAs involved in the regulation of muscle growth in patients hospitalized in intensive care (Bloch et al 2015). These findings suggest a direct role of GDF15 as a suppressor of muscle growth potentially involved in sarcopenia and, therefore, support GDF15 as a reliable biomarker.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…It was previously shown that overexpression of Gdf15 in mice prevents dietinduced obesity and increases lifespan by activating adipose tissue as well as systemic energy metabolism [66,67]. Conversely, circulating levels of GDF15 are also highly elevated in patients with muscle atrophy [68] and in cancer patients with severe anorexia and weight loss [69] and chronic inflammation [70]. Hence, future studies are required to delineate the protective or detrimental role of GDF15 as mitochondrial stress-induced cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Ligands from the transforming growth factor beta (TGF‐β) pathway are important regulators of muscle mass that are positively associated with muscle wasting in a variety of conditions. Both myostatin and growth differentiation factor 15 (GDF‐15) are elevated in a range of muscle wasting conditions and are able to promote atrophy . Myostatin promotes muscle wasting by activating the canonical TGF‐β signalling pathway via phosphorylation of SMAD proteins, leading to increased protein breakdown and autophagy .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the canonical TGF‐β signalling system in the control of muscle mass implies that miRNAs that alter the expression of components of the system will modify the sensitivity of individuals to atrophic signalling. For example, miR‐1 and miR‐181 suppress TGF‐β signalling either indirectly through the suppression of HDAC4 expression and the associated increase in follistatin expression in the case of miR‐1 or directly in the case of miR‐181 . As both miRNAs are suppressed by GDF‐15 in muscle, one effect of GDF‐15 will be to sensitize cells to TGF‐β and myostatin …”
Section: Introductionmentioning
confidence: 99%